YIELD AND NUTRIENTS UPTAKE OF SUNFLOWER (HELIANTHUS ANNUUS L.) AS INFLUENCED BY DIFFERENT LEVEL OF NITROGEN AND SULPHUR - B. BISWAS,; R. PODDAR, (The Bioscan, 2015)
An attempt was initiated during three consecutive rabi seasons during 2011-12 to 2013-14 at the farm of the Subdivision Adaptive Research Station, Nakasipara, Nadia, West Bengal, India to ascertain the response of nitrogen and sulphur on hybrid sunflower (Helianthus annuusL.). The experiment comprised four levels of nitrogen (50, 75, 100 and 125 kg N ha-1) and five levels of sulphur (0, 20, 30, 40, and 50 kg S ha-1) in factorial randomized block design replicated thrice. The seed yield increased significantly upto 100 kg Nha-1 (1816 kg ha-1) after that it declined. With the increasing level of sulphur, oil content (%) also increased. Application of sulphur upto 40 kg ha-1 increased the seed yield and thereafter it showed a decline trend indicating a quadratic fashion of response. Seed yield was found positively correlated with seeds capitulum-1 and 100-seed weight. Highest accumulation of nitrogen, sulphur, phosphorus and potasiumwas in head as compared with stem, leaf and petioles.Application of nitrogen upto 100 kg ha-1 and sulphurupto 40 kg ha-1would be required to realize satisfactory level yield in hybrid sunflower.